Outcome from the combined physician-surgeon diagnostic flexible airway endoscopy protocol for paediatric patients with severe airway problems - Asha'ari, Zamzil Amin; Abdullah, Fadzil; Yusof, Suhaimi; Yusof, Rosnida Azura (2014)
Objective: Flexible airway endoscopy is used by both physicians and surgeons to assess the airway. We analyze the yield from a physician-surgeon combined-care diagnostic flexible airway endoscopy protocol in children. Methods: Retrospective analysis of 121 procedures in 109 patients over more than a five-year period in an academic tertiary referral hospital. Inclusion criteria were children with severe airway problems and those who failed the initial airway endoscopy at the office settings. All patients underwent flexible airway endoscopy under topical anesthesia, with or without intravenous anesthesia. Results: 103 laryngobronchoscopic and 18 laryngoscopic examinations were performed in 109 patients (77 boys, median age 1.5 years). The main indications for flexible airway endoscopy were stridor (72.3%), followed by extubation/decannulation failure and chronic cough (5.8% each). Laryngomalacia (66 cases) was the most common diagnosis and the cause of 85.5% of cases of stridor. Twelve patients had multiple diagnoses. The diagnostic yield of flexible airway endoscopy was 89.3% (108 of 121). The yield was significantly related to the presenting symptoms (stridor/other), patient conditions (stable/unstable), and the underlying cause (congenital/acquired) (χ2, p<0.05). The management was changed from medical to surgical in 20.2% of cases. The average time from the flexible airway endoscopy to the surgical intervention was 18 hours. Treatment was initiated at least within one week of the diagnostic flexible airway endoscopy. Complications occurred in fourteen cases, but all were completely resolved. There was no death related to the procedure. Conclusion: Combined physician-surgeon flexible airway endoscopy gives a high diagnostic yield and potentially provides more efficient management of children with airway problems.